Associações sociotécnicas: mediações algorítmicas e a economia das ações no Facebook - Moura, Carolina Silva de (2018)
The project seeks to map the economy mediated by the association between the algorithms and the user on Facebook turning to the commercial pages.Economics keep a direct relationship with the processes of collecting, storing and articulating data favoring a personalization of content. The first part presents the project regarding the problem, objectives and your relevance. The second delivery of conceptual discussion about algorithms, their developments, research perspectives and which ones are sought in this analysis. The third one deals with the Theory-Actor Network, a theoretical proposal for research to consider symmetrical human and non-human highlightly Latour (1994a, 2012). Therefore, we explore ways of implementing empirical research based on the development of cartography (VENTURINNI, 2010; BARROS, KASTRUP, 2009; ROMAGNOLI, 2009; PRADO FILHO, TETI, 2013). Taking this as a reference, the empirical exercise was carried out from the profile of the researcher on Facebook for a month was observed on based on the selection of some internal and external variables about platform. The following reading exposes the data observed in this analysis that point to an economy based on the circulation of segmented contents based on the actions of the user, in which the user's action deals of algorithm transactions that reverberate is not that it is not News Feed and so the user also carries out their translations in a network that is made and remade in a constant way.